Computer Simulation of Earthing Systems under Variable Frequency and Transient Conditions (Comprehensive Journal of Science, 2026)
Earthing systems are essential for the secure dissipation of fault currents and those induced by lightning across a broad spectrum of frequencies, encompassing both power frequency and fast transient conditions. However, their behaviour at high frequencies is significantly influenced by inductive and capacitive effects, which are not adequately captured by conventional low-frequency design approaches. computer simulations were conducted to assess the high-frequency operational characteristics of earth electrode systems. The effect of electrode length has been simulated on the scaled 25mesh earth grid, with 5m x 5m dimensions. The results showed that the effective length is affected by soil resistivity and energisation characteristics such as frequency or impulse rise time. The effect of the downlead was also investigated, and it was found that length and path have a significant influence on impedance magnitude and transient potential rise values.To improve the performance under high frequency energisation, an insulated conductor will be bonded at the point of injection at one end and to positions out on the earth grid at the other end. The insulated horizontal enhancement will facilitate a diminution in the magnitude of impedance by enabling the dispersion of current to occur at a greater distance from the injection locus and by mitigating the inductive influence attributable to the supplementary parallel current pathways. The results underscore essential design parameters for contemporary earthing systems aimed at ensuring dependable functionality in the presence of lightning strikes and high-frequency environments. This paper presents an extensive numerical analysis of the transient and high-frequency behavior of vertical earth electrodes and earthing grids employing the CDEGS HIFREQ module.
Keywords: Earthing systems, Grounding, Soil Resistivity, High Frequency, Transient, Downlead, Effective Length, Effective Area